Half yard heaven : easy sewing projects using left-over pieces of fabric - Shore, Debbie (Writer on sewing) (Search Press, 2014)
Debbie Shore has a passion for sewing, and her fresh, contemporary designs coupled with simple, easy-to-follow instructions make this book a recipe for success. All of the projects use just half a yard (about half a metre) of fabric, making them ideal for using up scraps and oddments left over from other projects or sold off cheaply by your favourite fabric store. All you need is a sewing machine and a basic sewing kit, and in no time at all you'll be making one of the gorgeous projects in the book. There are twenty-six to choose from, including beautiful bags, aprons, a craft caddy for storing your making kit, padded coat hangers, a chicken doorstop, a handy wash bag, a notice board and numerous other gifts and accessories for you, your family and your home. The basic techniques you need to know are explained clearly at the beginning of the book, and every step-by-step project is accompanied by a fabulous photograph of the finished piece, which will not fail to delight and inspire you.